A tennis training application using 3D gesture recognition - García Bauza, Cristián; D'Amato, Juan; Vénere, Marcelo J.; Gariglio, Andrés; Abásolo Guerrero, María José; Manresa-Yee, Cristina; Mas-Sansó, Ramon (2012)
This paper presents a sport training system which recognizes user movements from data of the Wiimote device with accelerometer technology. Recognizing a new gesture involves the normalization of the Wiimote data and searching in a gesture templates database. The Dynamic Time Warping (DTW) comparison algorithm is used as a correlation function to compare the new gesture with every template. Based on prior training, the system can successfully recognize different sport shots. Particularly the system is instantiated for tennis training. The user visualizes the trajectory of the ball in a three-dimensional environment and he can interact with virtual objects that follow Newton dynamics.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Articulated Motion and Deformable Objects : 7th International Conference, AMDO 2012, Port d'Andratx, Mallorca, Spain, July 11-13, 2012. Proceedings. Berlín : Springer, 2012 (Lecture Notes in Computer Science ; 7378), pp. 239-249
Keywords: VIDEOJUEGOS; ENTRENAMIENTO DEPORTIVO; GRÁFICOS